Sosialisasi Pentingnya Pengembangan Potensi Daerah Untuk Meningkatkan Kesejahteraan Masyarakat Pada Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Dairi - Martin Luter Purba; Hanna M Damanik; Hendrik E.S Samosir (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2022)
This community service aims to provide recommendations for Dairi Regency in order to increase regional economic growth. Based on the results of the identification of the potential possessed by Dairi Regency, it can be seen that Dairi Regency has a great opportunity to increase its GRDP outperforming other regencies bordering the region if Dairi Regency has the potential of its human resources to be able to manage and develop the agricultural sector. This activity was carried out in the form of socialization which was attended by 25 representatives from the Camat, Lurah, Public Works and Spatial Planning and other relevant agencies in the Dairi Regency area. Through this activity, it is hoped that Dairi Regency can restore the wheels of the community's economy, especially after the pandemic so that the welfare of its people can increase. Keywords : increasing economic growth, increasing social welfare, agriculture